Discourses And Institutions In Tax Policy And Fiscal Sustainability: Evidence From Indonesia - Nur Arif Nugraha; Agung Darono (Jurnal Pajak dan Keuangan Negara (PKN), 2022)
This research contends fiscal policy and the achievement of fiscal sustainability as institutions coming from texts and discourses that account for it. Applying an interpretive policy analysis approach, we reveal how various discourses of tax policy and the achievement of fiscal sustainability dialectics. This study highlights some series of text-discourse-institution that explains the interplay between fiscal policy and the achievement of fiscal sustainability so that they become as main part of Indonesian public finance management. This paper finds that tax policy as an institution associates with the realization of fiscal sustainability is to increase the tax ratio while keep maintaining a self-assessment system. That is, the achievement of fiscal sustainability requires that tax policy can support (especially) to finance government expenditures. The study revealed that the contemporary tax policy as an institution, exists influenced by following discourses: (1) tax compliance strategy and taxing the hard-to-tax; (2) efforts to facilitate the strengthening of tax administration; (3) the establishment of information database as a tool to examine the compliance of taxpayers; (4) the division of taxing authority between central and local governments.